THE USE OF NON-VERBAL MEANS OF COMMUNICATION IN TEACHING ENGLISH - Холод, І.В. (SWorldJournal, 2022)
The article is devoted to the use of non-verbal means of communication in classes on English as a foreign language. The importance of non-verbal communication means in the transfer of information between the speaker and the recipient is substantiated. The